Assessment of rheological models for prediction of transport phenomena in stenosed artery. (28th October 2014) - Bit, Arindam; Chattopadhyay, Himadri
Hemodynamic transport in the stenosed blood vessel has been numerically investigated with five non-Newtonian rheological models. The results from Casson viscosity model, Carreau model, Cross model, power law viscosity model, and Quemada viscosity model as well as Newtonian model were compared to capture the physics at the arterial wall. At the inlet of a long artery, three different pulsating profiles are considered. Detailed flow statistics of the flow field were calculated by solving transient form of Navier-Stokes equation in an axi-symmetric domain. From the simulation data, wall shear stress and oscillatory shear index were calculated. The results show that among different rheological models, the predictions from Carreau model as well as Newtonian model differ significantly with other four models showing similar behaviour. The results demonstrate that the degree of stenoses have a significant effect on oscillatory shear index and recirculation length.